Influence of fabric anisotropy on seismic responses of foundations - Jin Qin; Xiangwu Zeng; Haiyan Ming (Journal of Rock Mechanics and Geotechnical Engineering, 2015)
Earthquakes, as one of the well-known natural disasters, are highly destructive and unpredictable. Foundation failure due to liquefaction induced by earthquakes can cause casualties as well as significant damage to the building itself. Fabric anisotropy of soil grains is considered to be an important factor in dynamic soil response based on previous researches and laboratory tests. However, the limited availability of real physical data makes it less persuasive. In this study, a shake table installed on a geotechnical centrifuge is used to provide the designed seismic motions, and therefore, to simulate the realistic earthquake motion to foundations. Important parameters in the responses such as acceleration, excess pore pressure and deformation are evaluated to investigate the influence. Implications for design are also discussed.